Estragole-rich essential oil of summer savory (Satureja hortensis L.) as an eco-friendly alternative to the synthetic insecticides in management of two stored-products insect pests - Asgar EBADOLLAHI (Acta Agriculturae Slovenica)
The lesser grain borer [Rhyzopertha dominica (Fabricius, 1792)] and the red flour beetle [Tribolium castaneum (Herbst, 1797)] are among the cosmopolitan damaging pests on several stored-products. The overuse of chemical pesticides in the control of such pests caused several side-effects including environmental contaminations, human health problems, and insect pests' resistance. In this circumstance, researchers have focused on safe and effective alternatives to chemical pesticides. In the present study, the insecticidal efficiency of essential oil extracted from the summer savory (Satureja hortensis L.) was assessed on the R. dominica and T. castaneum adults. The chemical profile of essential oil was evaluated through a gas chromatography-mass spectrometer, in which estragole, β-ocimene and d-limonene were the main components. The essential oil had considerable fumigant toxicity on insect pests. The mortality of insects was dependent on the essential oil concentration and exposure time. Probit analysis indicated that R. dominica with low LC50 values (Lethal Concentration to kill 50 % of tested insects) was more susceptible than T. castaneum. Accordingly, S. hortensis essential oil with a high level of phenylpropanoid and terpenic compounds can be recommended as an efficient and natural alternative to the detrimental chemicals in the management of R. dominica and T. castaneum.